Theatre improvisation training to promote social cognition: A novel recovery‐oriented intervention for youths at clinical risk for psychosis. Issue 2 (9th June 2019) - Tang, Sunny X.; Seelaus, Kevin H.; Moore, Tyler M.; Taylor, Jerome; Moog, Carol; O'Connor, David; Burkholder, Marla; Kohler, Christian G.; Grant, Paul M.; Eliash, Dvora; Calkins, Monica E.; Gur, Raquel E.; et al.
Abstract: Aim: Few interventions address social cognition or functioning in individuals at clinical risk (CR) for psychosis. Theatre Improvisation Training to Promote Social Cognition (TIPS) is a manualized intervention based on drama therapy. We aim to describe TIPS, evaluate feasibility and acceptability, and present a preliminary investigation of outcomes in a quasi‐experimental design. Methods: Thirty‐six CR participants (15‐25 years) were ascertained from the Philadelphia Neurodevelopmental Cohort. Twenty‐six completed the TIPS protocol: 18 weekly 2‐hour group sessions led by a theatre director and actor‐assistant. Participants engaged in collaborative acting and improvisation exercises. Baseline and follow‐up assessments included the Clinical Assessment Interview for Negative Symptoms (CAINS), Structured Interview for Prodromal Syndromes, Global Assessment of Functioning (GAF) and Penn Computerized Neurocognitive Battery (CNB), which includes social cognitive tests. Acceptability was assessed using focus groups. Preliminary outcomes were compared to CR controls who were not enrolled in the study but completed follow‐up assessments using the same methods. Results: There were no significant differences in baseline demographics, psychosis symptoms, or cognition between those who did and did not complete the protocol. Overall, TIPS was considered feasible and acceptable among CR. Preliminary outcomes suggest that TIPS may be effective in improving positive and negative psychosis‐spectrum symptoms and GAF, but not performance on facial emotion processing. Conclusions: TIPS is a promising and acceptable intervention that may improve symptoms and functioning in CR while providing a framework for participants to develop more empowered and confident ways of relating to others. Larger randomized controlled trials investigating TIPS efficacy are warranted.